Penerapan Metode 360 Derajat dalam Sistem Pendukung Keputusan Penentuan Jurusan SMA Berbasis Web (Studi Kasus: SMA Negeri 1 Salatiga) - Stefanie G. N. L. Worang; Natalia K. Toeera; Sylvia Lavinia; Andeka Rocky Tanaamah (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2013)
Nowadays decision support system becomes very important, because the decision support system can assist the management of an organization in decision making. Decision support systems can also be applied in schools, especially high school in the conscentration of students process. With the decision support system is expected to assist the school’s management to determine the concentration of students, especially this decision support system uses 360-degree method which based on multi-criteria according to concentration of students in high school that also has several criteria that should be considered.